The Contribution of Rapid Financial Development to Asymmetric Growth of Manufacturing Industries: Common Claims vs. Evidence for Poland - George M. von Furstenberg (Deutsche Bundesbank, 2004)
CEE countries such as Poland started to experience a very high rate of financial development within a few years after emerging from socialism. A review of the literature suggests that this asymmetric development should have been most beneficial for those industry sectors most dependent on external finance. However, the widelyused Rajan and Zingales (1998) measure of young (exchange-listed U.S.) companies' dependence on external finance had no explanatory power for the structure of industry growth in Poland. This negative finding held for 1990-2001 as a whole and for two distinct sub-periods that differed in the speed of financial development. Reasons for this failure, and correlates of the RZ measure, are examined.
Keywords: G20; O14; G22; O16; 330; Financial Development; Dependence on External Finance; Industry Structure; Poland; Finanzsektor; Finanzierung; Übergangswirtschaft; Unternehmensentwicklung; Fremdkapital; Industrieller Strukturwandel; Schätzung; Polen